2010
DOI: 10.1016/j.neuropsychologia.2010.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Early-life stress is associated with impairment in cognitive control in adolescence: An fMRI study

Abstract: Early-life stress (ES) has been associated with diverse forms of psychopathology. Some investigators suggest that these associations reflect the effects of stress on the neural circuits that support cognitive control. However, very few prior studies have examined the associations between ES, cognitive control, and underlying neural architecture. The present study compares adolescents with a documented history of ES to typical adolescents on a cognitive control task using functional magnetic resonance imaging (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
229
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(260 citation statements)
references
References 73 publications
23
229
1
7
Order By: Relevance
“…Human brain imaging studies subsequently showed that I‐ELT was associated with altered structural integrity in the limbic system (Aas et al., 2012; Andersen et al., 2008; Bremner et al., 1997; Carrion, Weems, & Reiss, 2007; Corbo et al., 2014; Dannlowski et al., 2012; Driessen et al., 2004; Lupien et al., 2011; Tottenham et al., 2010; Veer et al., 2015). Functional imaging studies have further shown that, when processing emotional stimuli (e.g., angry faces), I‐ELT was associated with increased activity in the amygdala (Bremner et al., 2005; Grant, Cannistraci, Hollon, Gore, & Shelton, 2011; Maheu et al., 2010), and with decreased activity of the hippocampus (Bremner et al., 1999; Bremner et al., 2003; Carrion, Haas, Garrett, Song, & Reiss, 2010) and anterior cingulate cortex (Bremner, Vythilingam, Vermetten, Southwick, McGlashan, Nazeer, et al., 2003; Bremner, et al., 2003; Bremner et al., 2004; Mueller et al., 2010). However, these studies have been limited by the consistent use of emotional stimuli, preventing assessments of whether I‐ELT‐related limbic dysfunction potentially impacts more general aspects of cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Human brain imaging studies subsequently showed that I‐ELT was associated with altered structural integrity in the limbic system (Aas et al., 2012; Andersen et al., 2008; Bremner et al., 1997; Carrion, Weems, & Reiss, 2007; Corbo et al., 2014; Dannlowski et al., 2012; Driessen et al., 2004; Lupien et al., 2011; Tottenham et al., 2010; Veer et al., 2015). Functional imaging studies have further shown that, when processing emotional stimuli (e.g., angry faces), I‐ELT was associated with increased activity in the amygdala (Bremner et al., 2005; Grant, Cannistraci, Hollon, Gore, & Shelton, 2011; Maheu et al., 2010), and with decreased activity of the hippocampus (Bremner et al., 1999; Bremner et al., 2003; Carrion, Haas, Garrett, Song, & Reiss, 2010) and anterior cingulate cortex (Bremner, Vythilingam, Vermetten, Southwick, McGlashan, Nazeer, et al., 2003; Bremner, et al., 2003; Bremner et al., 2004; Mueller et al., 2010). However, these studies have been limited by the consistent use of emotional stimuli, preventing assessments of whether I‐ELT‐related limbic dysfunction potentially impacts more general aspects of cognition.…”
Section: Introductionmentioning
confidence: 99%
“…These pathways center around 1), reduced cognitive control and self-regulatory abilities and 2), dysfunctional emotion processing. Although limited, on the one hand, previous work in individuals with experience of ES has documented impairments in cognitive control such as inhibition (Carrion, Garrett, Menon, Weems, & Reiss, 2008;De Bellis, Hooper, Spratt, & Woolley, 2009;Jovanovic et al, 2012;Lewis, Dozier, Ackerman, & Sepulveda-Kozakowski, 2007;Mueller et al, 2012), response shifting (Mueller et al, 2010), and working memory (Majer, Nater, Lin, Capuron, & Reeves, 2010).…”
mentioning
confidence: 99%
“…The early-life stress group took longer to switch from a prepotent response to an alternative response than the control group. Observation of neural activity revealed greater activation of several regions involved in cognitive control including the dlPFC and the striatum in the early-life stress group than in controls (Mueller et al, 2010). A previous study investigating the functional neuroanatomical correlates of response inhibition in thirty right-handed medication-naive youths (10-16 years, n=16) with post-traumatic symptoms (PTSS) and in a gender-matched control group of healthy youths (n=14) found that the PTSS subjects performed similarly to the control subjects in the Go/NoGo task.…”
Section: Traumatic Experiences Induce Functional Changes In the Prefrmentioning
confidence: 88%